Sustainable tourism and community participation in transfrontier tourism development : case of the Sengwe Community and the Great Limpopo Transfrontier Conservation Area (GLTFCA) - Saarinen, J.J. (2026)
Thesis (PhD (Tourism Management))--University of Pretoria, 2016.